Economical cat litter from biomass - Hasnan, Nur Syafiqah (2017)
Most commercially produced clay cat litters nowadays have raised issues to pet owners since they are nonbiodegradable and have no natural odor controlling features. In this study, biomass materials; sawdust and corn husk, were compared and processed into cat litter formulations due to their good absorption capacity and the biodegradability properties. Both biomass were dried to remove moisture content and grinded to reduce their particle size. Each of the raw materials were then mixed with clumping agent (xanthan gum), deodorizer (sodium bicarbonate), and dust retardant (glycerol) to form mixtures of cat litter. The mixtures were then dried and pelletized to reduce the dust formation. Eight cat litter formulations of sawdust and corn husk, including the blending of the raw biomass cat litter with their consecutive hydrogel biochar products and pure hydrogel biochars, as well as the commercial bentonite clay cat litter were tested in terms of their clumping activity, absorption capacity, and dust formation. Meanwhile, BET analysis was done to compare the surface area, total pore volume and average pore size of the sawdust cat litter, biochar, and hydrogel biochar.